Los sellos femeninos del entorno áulico de la Corona de Aragón (siglos XIII-XIV): ¿elementos de identidad, o piezas reivindicativas? - Serrano Coll, Marta (Eikón / Imago, 2025)
For some decades now, medievalism has been questioning about gender issues, but there is still a lot of work to be done, especially with regard to seals. This paper aims to clarify the state of new research focused on sigillography, a genre that, despite its relevance in the Middle Ages due to its legal and communicative value, has often been neglected by most of the historiography. Starting from the fundamental catalog made by Ferran de Sagarra in the first third of the 20th century, these lines exhaustively analyze, from a polyhedral point of view, the sigillar pieces opened by women in the Catalan territories of the Crown of Aragon between 1200 and 1400 to elucidate to what extent they became efficient and efficacious instruments of identity and vindication on the part of their female owners.